ANALISIS KETERAMPILAN LITERASI DIGITAL GURU PADA KETERAMPILAN MENULIS DAN MEMBACA DI SEKOLAH DASAR - Syfaul Hudiyah; Ermawati Zulikhatin Nuroh (Universitas Negeri Semarang, 2026)
Teachers' digital literacy skill is very important, especially in Indonesian language learning, because language material can be enriched through various digital media such as chat applications, social media, and online learning platforms. Digital literacy is not just technical skills in operating digital devices, but also critical thinking, interaction, collaboration, and innovation skills in a safe digital environment. This study uses a qualitative approach with a case study type. The case study type of research was used because this study examines in depth a specific case in a real context, namely the practice of digital literacy among teachers in elementary schools. The subjects of this study were two Indonesian language teachers at the public elementary school, namely the fourth-grade Indonesian language teacher and the fifth-grade Indonesian language teacher. The object of this study was the level of digital literacy skills of Indonesian language teachers at Trompoasri 2 Public Elementary School, in the form of skills in using, understanding, and creating digital literacy. The results of the study show that both teachers have integrated digital media such as PowerPoint, Canva, YouTube, and digital quizzes into their teaching. The fourth-grade teacher showed more varied and interactive use of media, while the fifth-grade teacher used digital media in a simpler but still relevant way. Teachers were able to adapt the media to the characteristics of their students, reflect on the effectiveness of technology use, and instill digital ethics and security. The obstacles encountered included limited internet access and infrastructure. In general, the teachers' digital literacy skills were in the good category, although strengthening in the aspects of critical evaluation of information sources and systematic optimization of technology use was still needed. This study provides practical contributions to the development of digital literacy competencies for elementary school teachers.